Interrelationship between storage protein, vitamin E and quality characteristics of selected South African bread wheat cultivars - Mkhatywa, Nomcebo Nomhle (University of the Free State, 2014)
The main objective of this study was to determine the relationship between protein fractions, vitamin E and quality characteristics in white flour and whole wheat flour grown at different geographical locations. Genotype, environment and G X E effect was highly significant for protein fractions as well as tocochromanols. Analysis of white flour and whole wheat in relation to baking quality performance showed that correlation may vary depending on characteristics. Most gliadins correlated negatively with important baking quality characteristics but some correlated positively with loaf volume, protein content and wet gluten content. A combined analysis shows positive correlations between LMW-GS and protein content, loaf volume and dough distensibility. Combined analysis of protein fractions also revealed that a high amount of high molecular weight polymeric proteins correlated with baking quality characteristics. Variability in content of tocochromanols was found among wheat cultivars from different environments. Caledon had the highest content of tocochromanols for both white and whole wheat flour. In this study it was shown that vitamin E does not compromise baking quality.

Die hoofdoel van hierdie studie was om die verhouding tussen proteïenfraksies en kwaliteitseienskappe met behulp van RP-HPLC en SE- HPLC te bepaal. Vitamien E (o.a. tocochromanole) inhoud van tien Suid-Afrikaanse brood koring kultivars is ondersoek. Genotipe, omgewing en G X E effek was hoogs betekenisvol vir proteïenfraksies sowel as tocochromanole. Ontleding vir wit meel en volgraan meel koring in verhouding tot die bak gehalte prestasie toon dat die korrelasies kan wissel, afhangende van eienskappe. Die meeste gliadien was negatief gekorreleer met belangrike bakkwaliteiteienskappe, maar sommige was positief gekorreleer met brood volume, proteïen-inhoud en nat gluten inhoud. 'n Gesamentlike ontleding toon positiewe korrelasie tussen lae molekulêre gewig - gluten subeenhede en proteïen-inhoud, brood volume en deeg vervormbaarheid. Gekombineer ontleding van proteïenfraksies het ook getoon dat 'n groot hoeveelheid van die hoë molekulêre gewig polimeriese proteïene korreleer is met van die bakkwaliteitseienskappe. Variasie in inhoud van tocochromanole is gevind onder die koring kultivars van verskillende omgewings. Caledon het die hoogste tocochromanol inhoud vir beide wit meel en volgraan meel gehad. In hierdie studie is getoon dat vitamien E nie bakkwaliteit benadeel nie.
Dissertation (M.Sc. (Plant Sciences: Plant Breeding))--University of the Free State, 2014
Keywords: High performance liquid chromatography; Wheat; Bread